PROSES BERPIKIR SISWA SMA DALAM PENYELESAIAN MASALAH APLIKASI TURUNAN FUNGSI DITINJAU DARI TIPE KEPRIBADIAN CHOLERIS - Rina Agustina (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The aims of the research is to describe the thinking process at senior high school students in solving the application problems of the derivative function viewedfrom personality type choleric. The research was a descriptive qualitative. The subjects of the research were students of class XII Senior High School 1 Surakarta, who has personality type choleric. The results of the research showed that thinking process students in solving the application problems of the derivative function for choleric student: (a) reading the problem and creating an image, understanding who is known to convert information into mathematical form, and looking the problem able to know the things in question, (b) devising the planning well, connecting the first equation with the planned solution, solving problem according to the planned solution but only using one way solution, (c) substituting the answers into the first equation and determining maximum value of the function